Children Nutritional Status Determinants in Rural East Nusatenggara - . Hardinsyah; Amini Nasoetion; Suprihatin Guhardja; Dadang Sukandar (Media Gizi dan Keluarga, 2000)
This study was aimed at analyzing nutritional determinant factors of under five year old children (UFC) in rural East Nusatenggara. The study used a data set of Agroecological Zone, Food and Nutrition Problems, which was designed as a cross-sectional study done by Department of Community Nutrition and Family Resources, Bogor Agricultural University. The data set count of 613 UFC from twenty-six villages of six districts. The districts and villages were selected purposively based on agroecological zones, and for each village, 20 to 25 households having UFC were selected randomly. Results from logistic regression analysis showed that underweight nutritional status associated with age of UFC and nutritional quality of the UFC¡¦S diet with odd ratio (OR) ranging from 1.6 to 2.1 (p